Alternative Substrate for Hypsizygus Tessellatus Cultivation - Thong, Weng Hing; Khu, Yong Ming; Geetha, Subramaniam (INTI International University, 2018)
The demand for mushrooms is increasing annually which opens an opportunity to developing countries to expand their mushroom industries as the mushroom culturing process converts agriculture waste to profit from crops. Hypsizygus tessellatus is a popular cultivated edible mushroom which is high in nutrient content and medicinal properties. This study was conducted to determine the effect of different parts of the stalk and different strength of potato dextrose agar (PDA) on the mycelium growth of H. tessellatus and to determine the effect of different alternative substrate, namely Dicranopteris linearis (fern leaf), dry leaf of Terminalia catappa and Imperata cylindrica (lalang grass) on the growth of shimeji mushroom, H. tessellatus. The mycelium from the upper and lower part of the mushroom stalk was cultured on half strength and full strength PDA, and the radius of the mycelium growth was measured. Mycelium from the lower part of the stalk had better growth effect. Full strength PDA also shown significantly better effects on mycelium growth. H. tessellatus were cultured on different types of substrate in capsule. Small pieces of D. linearis, I. cylindrica and dried leaf of T. catappa were found to be suitable alternative substrates for H. tessellatus cultivation where the mycelium growth in these substrate have no significant difference from the commercially used substrate which is mixture of saw dust and rice bran. The three alternative substrate mentioned above can be found in urban area in large amount which gave opportunity to people couldn’t gain access to the commercial substrate chance to collect their own substrate for mushroom cultivation.